The Influence of Office Facilities on Employee Performance in the One-Stop Single Administration System (Samsat) Office in Gowa Regency. - Annisa Sultan; Sitti Nurbaya; M. Yusuf Alfian Rendra Anggoro (GoodWill, 2026)
This study examines the influence of office facilities on employee performance at the One-Stop Single Administration System (SAMSAT) Office in Gowa Regency, Indonesia. The study employed a quantitative research approach to analyze the relationship between office facilities and employee performance. Data were collected through direct observation, documentation, and structured questionnaires distributed to all employees of the SAMSAT Office using a saturated sampling technique. A total of 43 employees participated as respondents. The research instrument utilized a Likert scale and the collected data were analyzed using simple linear regression with the assistance of Statistical Package for the Social Sciences (SPSS) version 27. The findings reveal that office facilities have a positive and significant effect on employee performance. The regression analysis produced a coefficient value of 0.789 with a significance level of 0.000, indicating that improvements in office facilities contribute substantially to enhanced employee performance. The coefficient of determination (R²) value of 0.598 demonstrates that 59.8% of employee performance variation can be explained by office facilities, while the remaining 40.2% is influenced by other variables outside the scope of this study. The results highlight the importance of adequate office infrastructure, equipment availability, workspace arrangement, and technological support in improving work efficiency, productivity, and service quality within public sector organizations. Therefore, enhancing office facilities should become a strategic priority for improving employee performance and organizational effectiveness at the SAMSAT Office in Gowa Regency.